Meningkatkan Kompetensi Digital Guru SD melalui Pelatihan Desain Modul Ajar Kreatif dengan Canva di Kota Jambi - Renny Afriany; Samsinar Samsinar; Rudolf Sinaga; Frangky Frangky; Ika Widyastuti (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service activity aims to improve the digital competence and creativity of elementary school teachers in Jambi City through training in making teaching modules using the Canva platform. The main problem faced by teachers is the limited ability to design digital teaching materials that are attractive and in accordance with the demands of the Independent Curriculum. The training was held at SD Negeri 176 Jambi City on July 30, 2025 with interactive lectures, direct demonstrations, and independent practice. Participants consisted of elementary school teachers from several schools in Jambi City. Training materials include an introduction to Canva, the basic principles of educational graphic design, the creation of learning outcomes-based learning modules, and the publication of design results. Evaluation is carried out through pre-test and post-test, observation of participant activities, and assessment of the digital teaching module products produced. The results of the evaluation showed a significant improvement in participants' understanding and skills, with more than 90% of participants experiencing an increase in scores, and 85% stating that they would use Canva regularly in the preparation of teaching materials. In addition, participants showed high enthusiasm and produced teaching modules that were creative and contextual to the needs of students. This activity contributes to strengthening pedagogic competence, digital literacy, and learning innovation in the basic education environment, as well as being a concrete step to support the digital transformation of education in Jambi City.